Safety of lignosulphonate for all animal species. (12th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of lignosulphonate, when used as a technological additive, functional group: binders. In a previous opinion, the FEEDAP Panel could not conclude on the safety of the additive for target species and for the environment. The applicant provided additional information that was assessed in the current opinion. As regards the safety for the target species, the maximum recommended content of lignosulphonate of 10, 000 mg/kg complete feed is considered safe in weaned piglet. A safe concentration of lignosulphonate in feed for salmonids and dairy cows could not be identified. The FEEDAP Panel reiterates also its previous conclusions that '10, 000 mg lignosulphonate/kg complete feed is safe for chickens for fattening, laying hens and cattle for fattening but a margin of safety cannot be identified. Therefore, this conclusion cannot be extended to all animal species/categories'. Considering the absence of adverse effects confirmed by all the ecotoxicity studies up to very high concentrations, no concerns for the environment are expected from the use of this additive in animal nutrition according the conditions of use. Lignosulphonate is efficacious as pellet binder.